Diffusion of Environmental Norm from International to Subnational Level: Promotion of Circular Economy Practices on Waste Management in Samarinda, East Kalimantan - Ridho, Muhammad Rasyid; Maghfiroh, Melati Ning (FEB Universitas Mulawarman, 2025)
This study examines how the circular economy (CE) as an environmental norm spread from international institutions to subnational levels, focusing on waste management practices in Samarinda, East Kalimantan. Using Finnemore and Sikkink’s (1998) norm life-cycle framework, the research analyses the process of norm emergence, cascade, and internalization. Data were collected through desk research and interviews with PT Asiana Recycle Indonesia (PT ARI), a local private actor in waste management. The study finds that international organizations such as the Ellen MacArthur Foundation, the European Union (EU), and the World Economic Forum (WEF) play key roles in promoting CE globally through policies and programs. Indonesia has adopted related norms through national regulations and cooperation with foreign partners, yet its implementation remains limited to basic 3R practices. At the local level, Samarinda shows partial internalization of CE principles, supported by local regulations and community waste banks. PT ARI serves as a norm internalization actor as well as local norm entrepreneur by applying CE ideas through recycling initiatives and public awareness programs. CE diffusion in Samarinda demonstrates a gradual but uneven process of translating global norms into local practices, requiring stronger policy integration and cooperation among stakeholders